2018
DOI: 10.3389/fict.2018.00023
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback for Everyday Stress Management: A Systematic Review

Abstract: Background: Mainly due to an increase in stress-related health problems and driven by recent technological advances in biosensors, microelectronics, computing platform, and human-computer interaction, ubiquitous physiological information will potentially transform the role of biofeedback in clinical treatment. Such technology is also likely to provide a useful tool for stress management in everyday life. The aim of this systematic review is to: (1) Classify biofeedback systems for stress management, with a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 88 publications
(209 reference statements)
1
90
0
3
Order By: Relevance
“…These effects are best achieved if the voluntary modulation of breathing is performed via respiratory biofeedback, which facilitates the maintenance of a given breathing pace or the execution of specific breathing exercises. f R is a fundamental variable for any respiratory biofeedback strategy, but other ventilatory variables may also prove useful, such as V T , inspiratory time, and expiratory time [274,275]. The primary role of f R in respiratory biofeedback is given by the marked effect of its change on different physiological systems, including the modulation of heart rate variability, which is particularly effective at f R values around 6 breaths/min [276].…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…These effects are best achieved if the voluntary modulation of breathing is performed via respiratory biofeedback, which facilitates the maintenance of a given breathing pace or the execution of specific breathing exercises. f R is a fundamental variable for any respiratory biofeedback strategy, but other ventilatory variables may also prove useful, such as V T , inspiratory time, and expiratory time [274,275]. The primary role of f R in respiratory biofeedback is given by the marked effect of its change on different physiological systems, including the modulation of heart rate variability, which is particularly effective at f R values around 6 breaths/min [276].…”
Section: Current Evidencementioning
confidence: 99%
“…It has even been suggested that the effect of respiratory modulation on heart rate variability is maximized when f R is set at the so-called individual resonant frequency, but more research is needed to further test this hypothesis [276]. Respiratory biofeedback is usually delivered by sound output and/or visual feedback, including attractive forms like music and biofeedback games [275,277,278]. It is a very useful technique to learn respiratory skills and exercises (e.g., diaphragmatic breathing) [271], especially for less compliant individuals like children and older adults.…”
Section: Current Evidencementioning
confidence: 99%
“…Biofeedback could be used to investigate well-established psychophysiological effects in environments that provide a higher degree of generalizability to everyday life than traditional experimental designs. A few examples could be studying (through training) the role of easily measurable markers like heart-rate variability for stress management (Yu, Funk, Hu, Wang, & Feijs, 2018) or anticipatory bradycardia for decision making (Roelofs, 2017). In these two specific examples, studying the contribution of well-established psychophysiological markers in generalizable contexts would pave the way for a wide range of affordable interventions aiming at changing, for example, the behavior of patients suffering from anxiety disorders.…”
Section: Extending the Use Of Srd To Other Methodsmentioning
confidence: 99%
“…Assessment is carried out during the interaction of children suffering from Specific Learning Disorders (SLD) with the HapHop-Physio system. Both physiological signals are good indicators of cognitive changes [13]- [15]. The final aim of this paper is going towards the validation of the relationship between cognition (as the class) and changes in these signals (as attributes), demonstrating the feasibility of a machine learning classification approach in a three-class classification task (low, medium, and high performance).…”
Section: Introductionmentioning
confidence: 95%